1999
DOI: 10.1016/s0893-133x(98)00084-0
|View full text |Cite
|
Sign up to set email alerts
|

Reinstatement of Alcohol-Seeking Behavior by Drug-Associated Discriminative Stimuli after Prolonged Extinction in the Rat

Abstract: (Wikler 1948). There is now ample evidence that conditioned stimuli associated with the availability or consumption of abused drugs enhance subjective feelings of craving and the motivation to engage in drug-taking behavior in humans (Childress et al. 1987a(Childress et al. , 1987b(Childress et al. , 1988O'Brien et al. 1990O'Brien et al. , 1992Ehrman et al. 1992;Kranzler and Bauer 1992;Robbins and Ehrman 1992). For example, abstinent alcohol users exposed to a bar-like environment worked (i.e., pressed a butto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
109
3
4

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(132 citation statements)
references
References 35 publications
16
109
3
4
Order By: Relevance
“…Our reinstatement results confirm that environmental stimuli previously associated with and predictive of ethanol availability reliably reinstate extinguished responding at a previously ethanol-paired lever (Ciccocioppo et al, 2001;Katner et al, 1999). The behavioral effects of the ethanolassociated stimuli proved highly resistant to extinction as reflected by the stability of conditioned ethanol-seeking behavior over the repeated reinstatement testing.…”
Section: Discussionsupporting
confidence: 77%
“…Our reinstatement results confirm that environmental stimuli previously associated with and predictive of ethanol availability reliably reinstate extinguished responding at a previously ethanol-paired lever (Ciccocioppo et al, 2001;Katner et al, 1999). The behavioral effects of the ethanolassociated stimuli proved highly resistant to extinction as reflected by the stability of conditioned ethanol-seeking behavior over the repeated reinstatement testing.…”
Section: Discussionsupporting
confidence: 77%
“…When the CS is subsequently presented again, conditioned responding is evoked. Reinstatement has been demonstrated following extinction of fear conditioning in rats (e.g., Rescorla & Heth, 1975;Westbrook, lordanova, McNally, Richardson, & Harris, 2002) as well as in operant conditioning procedures involving drug-reinforced operant responding (e.g., de Wit & Stewart, 1981Stewart, , 1983Katner, Magalong, & Weiss, 1999;McFarland & Ettenberg, 1997). However, there are no known studies that have reported reinstatement of discriminated operant responding under discriminative control by drugs by noncontingent reinforcement following extinction.…”
Section: Methodsmentioning
confidence: 99%
“…Animals trained to lever press for access to alcohol in the presence of auditory or visual cues will not necessarily reinstate lever pressing to these cues after extended extinction (Katner et al 1999; see also Bienkowski et al 2000). However, non-contingent "priming" with alcohol reinstates responding on the "alcohol bar" (Chiamulera et al 1995; see review by .…”
Section: Repeated Alcohol Withdrawals and The Alcohol-deprivation Effmentioning
confidence: 99%
“…However, non-contingent "priming" with alcohol reinstates responding on the "alcohol bar" (Chiamulera et al 1995; see review by . Likewise, when exposed to a combination of an olfactory cue for alcohol and a previously presented auditory or visual cue (Katner et al 1999;Bienkowski et al 2000), alcohol-seeking behavior is reinstated. An alternative approach to facilitate motivation for alcohol after extinction is to induce alcohol dependence prior to testing Liu and Weiss 2002a,b).…”
Section: Repeated Alcohol Withdrawals and The Alcohol-deprivation Effmentioning
confidence: 99%